Utopian biologies. Issue 1 (7th March 2018) - Endersby, Jim
Abstract : In 1924, the British biologist J.B.S. Haldane acknowledged that anyone who tried to predict where science was taking us was obliged to mention H.G. Wells, since '[t]he very mention of the future suggests him'. Nevertheless, Haldane complained that Wells was 'a generation behind the time', having been raised when flying and radiotelegraphy were genuinely scientific questions, but they were now mere 'commercial problems', Haldane asserted, and 'I believe that the centre of scientific interest lies in biology'. Haldane's conviction that biology was the key to the future was widely shared, and lies in the background of both these books. Helen Curry examines the early history of the dream of engineering new kinds of plants, using first X-rays, then colchicine (a chemical mutagen), and then the new sources of intense radioactivity that were created by the early nuclear reactors. By contrast, Ewa Luczak is interested in the influence of eugenics on American literature, focusing particularly on Jack London, Charlotte Perkins Gilman and George Schuyler. What unites these books (and the diverse topics they address) is new ways of imagining the future, specifically a future based in biology.